2018
DOI: 10.4310/jdg/1518490817
|View full text |Cite
|
Sign up to set email alerts
|

Green function, Painlevé VI equation, and Eisenstein series of weight one

Abstract: We study the problem: How many singular points of a solution λ(t) to the Painlevé VI equation with parameter ( 1 8 , −1 8 , 1 8 , 3Based on Hitchin's formula, we explore the connection of this problem with Green function and the Eisenstein series of weight one. Among other things, we prove:(i) There are only three solutions which have no singular points in C \ {0, 1}. (ii) For a special type of solutions (called real solutions here), any branch of a solution has at most two singular points (in particular, at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 29 publications
(62 reference statements)
1
60
0
Order By: Relevance
“…The reason why we choose the fundamental domain F 0 will be clear from the proof, particularly Lemma 2.3. The basic strategy is similar to that of proving Theorem A in [6]. However, the argument is more involved and new techniques are needed.…”
Section: Zeros Of Pre-modular Formsmentioning
confidence: 99%
“…The reason why we choose the fundamental domain F 0 will be clear from the proof, particularly Lemma 2.3. The basic strategy is similar to that of proving Theorem A in [6]. However, the argument is more involved and new techniques are needed.…”
Section: Zeros Of Pre-modular Formsmentioning
confidence: 99%
“…Remark 2.3. Recently, Chen, Kuo, Lin and Wang in [36] showed that G(z) might have an extra pair of "non-trivial" critical points other than the three half periods points for a class of flat tori. Moreover, the "non-trivial" critical points are always non-degenerate.…”
Section: Preliminariesmentioning
confidence: 99%
“…all solutions of (1.11) are free of logarithmic singularity at any singular point. See [4,5,7,18] for recent developments of (1.11). Like (1.2), we could associate a hyperelliptic curve Γ n,p (τ ) := {(A, W )|W 2 = Q n,p (A; τ )} and an addition map σ n,p with (1.11).…”
Section: Introductionmentioning
confidence: 99%